Edukasi Dan Praktik Pemenuhan Gizi Seimbang Ibu Hamil - Leni Sri Rahayu; Izza Suraya; Nur Syifa Maulida (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2022)
The fulfillment of pregnant women's nutrition is important during their pregnancy. By getting balanced and good nutrition, pregnant women can reduce health risks to their fetus, such as stunting. However, less intake in pregnant women is still found in the RW 06, Lubang Buaya, East Jakarta.  Therefore, appropriate intervention is needed to prevent its problem.  Intervention is carried out in the form of community service and aims to improve the knowledge and skills of pregnant women in providing and consuming a balanced diet. The methods used are talk show, virtual counseling, and self-practice of making a balanced and nutritious menu. The number of pregnant women has reached the target (20 people).  After these activities, there was an increase in their knowledge by 1,6. Based on skills, all participants have succeeded in practicing the balanced and nutritional menu at their home.